Teaching Life Skills to Students with Disabilities in Physical Education: Publication Trend in the Last 51 Years - Razali Razali; Mansur Mansur; Jusuf Blegur; Berliana Berliana; Muhamad Ilham; Muhammad Nur Alif; Iis Sintiani; Mieke Souisa; Ade Evriansyah Lubis; Zuvyati Aryani Tlonaen (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Life skills have been proven to help students overcome various problems. Therefore, they have been integrated into various student learning activities. However, have life skills also been integrated into physical education teaching for students with disabilities? This study aims to investigate the bibliometric publication of articles on teaching life skills to students with disabilities in physical education. The inspection was conducted on June 1, 2024, based on the Scopus platform using the term "teaching life skills to students with disabilities in physical education" with the doc-type article, review, and conference paper. In addition to using the Scopus analysis engine, researchers used metric analysis from Publish or Perish and visualization analysis from VOSviewer. Over the past 51 years, researchers have only managed to publish 18 Scopus documents on teaching life skills in physical education for students with disabilities. In addition, from the keyword corpus, only the keyword "disability" has networking with the keyword "daily life activity," unfortunately the networking is the furthest from other keywords. Meanwhile, from the title and abstract corpus, the term "life skills" was not found in the networking map. Thus, teaching life skills in physical education for people with disabilities has not received serious attention from researchers worldwide, so future studies on teaching life skills in physical education for people with disabilities have great potential to be explored. Future investigations can expand data collection platforms beyond Scopus, such as WoS, ERIC, DOAJ, and others, to gather more comprehensive data in discussing life skills teaching for students with disabilities in physical education.